2011
DOI: 10.1002/ar.21394
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Nitrergic Neurons in the Dorsal Root Ganglia of the Bottlenose Dolphin (Tursiops truncatus)

Abstract: Dorsal root ganglia (DRGs) contain the cell bodies of primary afferent neurons that transmit sensory information from the periphery into the spinal cord. Distinct populations of DRG neurons have been characterized by a variety of different immunohistochemical markers. A subpopulation of ganglionic neurons containing neuronal nitric oxide synthase (nNOS), an enzyme known to generate nitric oxide, has been detected in a number of mammalian species. Despite previous studies, no information is known on the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…In agreement with the previous data, pharmacological studies revealed that different spinal functional processes, such as nociceptive transmission, central sensibilization, and hyperanalgesia, require the production of NO (Meller et al, 1992;Meller and Gebhart, 1993;McMahon et al, 1993). In the bottlenose dolphin, the involving of NO on nociceptive transmission is also suggested from a recent study indicating that the majority of nitrergic neurons of the spinal ganglia express Substance P (SP) (Bombardi et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In agreement with the previous data, pharmacological studies revealed that different spinal functional processes, such as nociceptive transmission, central sensibilization, and hyperanalgesia, require the production of NO (Meller et al, 1992;Meller and Gebhart, 1993;McMahon et al, 1993). In the bottlenose dolphin, the involving of NO on nociceptive transmission is also suggested from a recent study indicating that the majority of nitrergic neurons of the spinal ganglia express Substance P (SP) (Bombardi et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…As reported in previous studies, the NADPH-d reaction and the mouse anti-nNOS marked the same neurons (Dawson et al, 1991;Vincent and Kimura, 1992;Giraldi-Guimarães et al, 1999;Bombardi et al, 2006Bombardi et al, , 2011. In the bottlenose dolphin, the laminar distribution of the spinal nitrergic neurons is similar to that reported in mouse, rat, rabbit, dog, cat, and Primates, with somata localized with a high density in Laminae I, II, VII (intermediolateral cell column and nucleus intermediolateralis sacralis of terrestrial Mammals), and X (Br€ uning, 1992;Dun et al, 1992Dun et al, , 1993Valtschanoff et al, 1992a,b;Spike et al, 1993;Terenghi et al, 1993;Saito et al, 1994;Vizzard et al, 1994;Wetts and Vaughn, 1994;Pullen and Humphreys, 1995;Mars ala et al, 1998Mars ala et al, , 1999Kluchov a et al, 2000).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations